Effect of gender, biochemical parameters & parathyroid surgery on gastrointestinal manifestations of symptomatic primary hyperparathyroidism - Viral N Shah (Indian Journal of Medical Research, 2014)
Background & objectives: Information on gastrointestinal manifestations and then response after curative parathyroid surgery is scarce in symptomatic primary hyperparathyroidism (PHPT). This study was carried out to analyse gastrointestinal manifestations in patients with PHPT and their associations with biochemical parameters. Methods: This retrospective study included 153 patients with symptomatic primary hyperparathyroidism (PHPT). The signs and symptoms pertaining to gastrointestinal system were analyzed. The difference of symptoms between men and women and difference in biochemical parameters in presence of different symptoms were evaluated. The relationship between serum calcium, phosphate and parathyroid hormone (PTH) levels with presence of gallstone and pancreatitis was also studied. Result: Of the 153 patients, 46 (30%) were men. The mean age was 39.2 ± 13.9 yr. Nearly 80 per cent of PHPT patients had at least one symptom/ sign related to gastrointestinal system. The most common gastrointestinal manifestations were abdominal pain 66 (43%), constipation 55 (36%), and nausea/or vomiting 46 (30%). Nearly one-fourth 34 (22%) of patients had a history of either gallstone disease or cholecystectomy or both. The prevalence of gallstone disease was higher in women (P<0.05). Imaging and biochemical evidence of pancreatitis was found in 27 (18%) patients. Pancreatitis was more common in men compared to women (P<0.05) despite the higher prevalence of gallstones in women. Serum calcium, phosphate or PTH levels were not associated with high risk for gallstone disease, however, serum calcium (P<0.05) was associated with 1.3 times higher risk of developing pancreatitis. In majority of patients, gastrointestinal manifestations resolved within three months of curative parathyroidectomy. Except two patients, none had recurrence of pancreatitis. Interpretation & conclusions: The study revealed that the gastrointestinal symptoms were common in patients with symptomatic PHPT. There was not much gender difference in gastrointestinal symptoms except higher occurrence of gallstones in women and pancreatitis in men. There was no difference in biochemical profile between those who had and did not have gastrointestinal symptoms.